Evaluation of Different Collections of Mucuna pruriens for Morphological Parameters and L-dopa Yield - Chandra, Puran; Rana, R. C.; Mehra, T. S.; Raina, R. (Indian Forester, 2011)
Mucuna pruriens, commonly known as Konch or Cowhedge is a traditionally used medicinal plant. Seeds of the species contain high percentage of active principle L-DOPA, which is used for curing Parkinson disease. There is a great variation in the seed colour of the species, and in the present study twenty eight black mottled with brown (collected locally) and creamish white (procured form NBPGR New Delhi) seeds were evaluated for morphological parameters as well as for L-DOPA content. Black seeded collections were found to contain high level of L-DOPA ranging 6.36 to 7.30. But, the seed yield and consequently L-DOPA yield was low ranging 38.40-65.86g and 2.35-4.69g per plant respectively Moreover, pods of these collections contain itching trichomes which puts workers in commercial cultivation Among black seeded collections regarding seed yield, L-DOPA content and L-DOPA yield collections Panba, Nagrota, Jwalaji Hilltop and Jwalaji excelled over all other collections. L-DOPA content in white seeded collections was low ranging 5.41-5.78 per cent. But, the seed yield and consequently L-DOPA yield was very high ranging 4.30-697.20g and 23.38-39.73g respectively. Also, pods of these collections are devoid of itching trichomes. Among white seeded collections regarding seed yield, L-DOPA content L-DOPA yield collection IC127363 and IC 127362 excelled over other collections. Exotic collection EC 144945 performed below par for all the parameters studied.